Assessing the Cognitive Impact of Insomnia: A Case Study of a Young Adult - Sexton-Radek, Kathy (Medical Science: Trends and Innovations Vol. 10, 2025)
Sleep is the most significant factor for keeping young adults healthy and active. Sleep deprivation increases the risk of depression, anxiety, and low self-esteem. Sleep is essential for the mental, physical, social, and emotional development of young adults. Sleep deprivation may cause impairment in cognition and emotions among young adults. A case study is used to illustrate cognitive factors related to poor sleep quality in a young adult. The participant was a healthy patient outside of his sleep disturbance. Changes in cognitive functioning were evaluated with the Repeatable Battery for Assessment of Neuropsychological Status (RBANS). RBANS is a series of 12 subtests that provide a broad selection of tasks that measure neuropsychological impairment. The RBANS was administered during intake, one month and at six months following the eight weeks of Cognitive Behavior Therapy. The profile of performance for the participant was similar to that previously reported for mild cognitive impairment due to head trauma. The implication to health (i.e., cognitive functioning) for sleep disturbance is presented. The outcome shows cognitive abilities such as language skills improved as sleep efficiency increased, whereas other cognitive abilities such as immediate and delayed memory did not show improvement. The implication is that sleep disturbance and poor quality of sleep can impact one’s cognitive functioning and are related to overall health and well-being.